2008
DOI: 10.1038/modpathol.2008.105
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA analysis as a potential diagnostic tool for papillary thyroid carcinoma

Abstract: MicroRNA (miRNA) microarray analysis has consistently found altered expression of miRNAs in thyroid tumors, suggesting their roles in thyroid carcinogenesis. To explore whether this differential expression can be used as a diagnostic tool in surgical pathology and fine-needle aspirate (FNA) specimens, the expression of selected miRNA was evaluated by quantitative RT-PCR, using total RNA from 84 formalin-fixed paraffin-embedded tissues and 40 ex vivo aspirate specimens. miRNA from all paraffin-embedded tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
152
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 49 publications
8
152
0
11
Order By: Relevance
“…As for diagnostic purposes, only miRNA 146b reliably distinguish the conventional and tall cell variant from benign thyroid lesions in individual cases, whereas all other miRNAs show substantial overlap. This is in accordance with a study by Chen et al (2008) who found miRNA 146b to be most consistently overexpressed in both conventional and follicular variants when compared with 'borderline' follicular lesions, although the number of five follicular variants in their study is rather small.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As for diagnostic purposes, only miRNA 146b reliably distinguish the conventional and tall cell variant from benign thyroid lesions in individual cases, whereas all other miRNAs show substantial overlap. This is in accordance with a study by Chen et al (2008) who found miRNA 146b to be most consistently overexpressed in both conventional and follicular variants when compared with 'borderline' follicular lesions, although the number of five follicular variants in their study is rather small.…”
Section: Discussionsupporting
confidence: 79%
“…In accordance with previous studies (He et al, 2005;Pallante et al, 2006;Tetzlaff et al, 2007;Chen et al, 2008;Nikiforova et al, 2008) the analysis of a limited set of miRNAs represents a reliable method to distinguish PTC from benign thyroid lesions (for review see Table 1). Considering the mean DCt values of all miRNAs analysed in our study, we showed highly significant changes between PTC and MNG/FA.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, among the targets of miR-486-5p, there is PIK3R1 that is known to be upregulated in responsive patients after cetuximab treatment (39). miR146b-3p has been reported to be an unfavorable cancer prognostic marker for patients with squamous cell lung cancer or papillary thyroid carcinoma (40)(41)(42). Interestingly, its upregulation is statistically associated with BRAF mutation in papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Both FISH and RT-PCR have been shown to be very useful when searching for specific neoplasiaassociated rearrangements, such as fusion genes, in samples with small numbers of tumor cells [11,12]. are some promising results on FNA material from papillary thyroid carcinoma and non-small cell lung carcinomas [13][14][15]. The same techniques should be applicable also to soft tissue and bone tumors, but further studies are needed to evaluate this.…”
Section: Discussionmentioning
confidence: 99%